Cost-effectiveness of Antipsychotics in Treatment of Schizophrenia Patients admitted to a secondary Hospital - Andriani, Yuni; Septiani, Frisca Nindy; Defirson, Defirson (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Abstract. Schizophrenia is a chronic disease that requires relatively high treatment costs [1]. Several studies have found that atypical antipsychotics are more effective compared to typical antipsychotics. As a result, the duration of treatment and the patients’ length of hospital stay will be shorter which ultimately reduce the overall treatment costs. Therefore, it is necessary to conduct a cost-effectiveness analysis (CEA) of the two classes of antipsychotic drugs in the treatment of schizophrenia inpatients admitted to Jambi Province Hospital period 2013-2016. Method: This descriptive retrospective cohort study was undertaken to analyze cost-effectiveness of the antipsychotic drugs provided to patients with schizophrenia (n=910) admitted to Jambi Province Hospital from the perspective of a healthcare provider. using purposive sampling technique. Characteristics of the patients, antipsychotic drugs usage, costs consumed, and treatment outcome were extracted from the hospital databases. Results: It was found that the total ACER value of the typical antipsychotic group was Rp. 142,789.25 and atypical antipsychotics is IDR 163,045.50 which indicates that the typical ACER antipsychotic value is smaller than those of atypical antipsychotics based on the length of stay of patients in the Psychiatric Intensive Care Unit (PICU) room. Whereas based on the PANSS-EC score of the patient, the total ACER value of the typical antipsychotic group was IDR1,189,910.42 and in atypical antipsychotics was IDR. 572,089.47. Conclusion: Atypical antipsychotics are more cost-effective than typical antipsychotics.